Peripartum cardiomyopathy: current theories about etiopathogenesis, potential biomarkers and treatment - a literature review - Zielonka, Bartłomiej; Kowalczyk, Ilona; Stawikowski, Cezary; Wolanin, Marta; Wolanin, Izabela; Stachyra, Bartłomiej; Krawiec, Paulina; Madej, Karolina; Osińska, Aleksandra; Dengler, Barbara (Journal of Education, Health and Sport, 2023)
Background: Peripartum cardiomyopathy (PPCM) is a form of an idiopathic systolic heart failure, which occurs the most often in the last weeks of pregnancy or in the early postpartum period. Symptoms of this disease include exertional dyspnea, orthopnoea, paroxysmal nocturnal dyspnoea and edema. They are typical for a heart failure, but also can be attributed to late pregnancy or the effects of labor, which is a cause of common misdiagnosis or its delay and significantly affects the worsening of the prognosis and the high mortality rate. In more severe cases, cardiogenic shock, arrhythmias, thromboembolic complications may occur, leading to death. Aim of the study: The study aim is to summarize the current state of knowledge and the recent scientific reports on the potential etiopathogenesis, diagnostics including new biomarkers, and treatment of the peripartum cardiomyopathy. Material and methods: The study is based on the scientific literature available in the PubMed and Google Scholar databases, using the following keywords: „peripartum cardiomyopathy”, „pregnancy-associated cardiomyopathy” and “16-kDa prolactin”. Results and conclusions: The diagnosis of peripartum cardiomyopathy should be considered in every pregnant or postnatal woman with symptoms of heart failure. Despite great advances made in understanding and diagnosing PPCM over the last few years, the pathogenesis and complex interactions of genetics and the vascular and hormonal balance of late pregnancy are still unclear. Further research is needed to determine the benefits and risks of bromocriptine treatment and the use of new markers in the diagnostics of PPCM.